Nano-Drug Delivery Systems Entrapping Natural Bioactive Compounds for Cancer: Recent Progress and Future Challenges - Chavda, Vivek P.; Patel, Aayushi B.; Mistry, Kavya J.; Suthar, Suresh F.; Wu, Zhuo-Xun; Chen, Zhe-Sheng; Hou, Kaijian (Frontiers in Oncology, 2022)
Cancer is a prominent cause of mortality globally, and it becomes fatal and incurable if it is delayed in diagnosis. Chemotherapy is a type of treatment that is used to eliminate, diminish, or restrict tumor progression. Chemotherapeutic medicines are available in various formulations. Some tumors require just one type of chemotherapy medication, while others may require a combination of surgery and/or radiotherapy. Treatments might last from a few minutes to many hours to several days. Each medication has potential adverse effects. Researchers have recently become interested in the use of natural bioactive compounds in anticancer therapy. Some phytochemicals have effects on cellular processes and signaling pathways, as well as having antitumor properties. Beneficial anticancer effects of phytochemicals were observed in both in vivo and in vitro investigations. Encapsulating natural bioactive compounds in different drug delivery methods may improve their anticancer efficacy. Greater in vivo stability and bioavailability, as well as a reduction in undesirable effects and an enhancement in target-specific activity, will increase the effectiveness of bioactive compounds. This study will focus on a novel drug delivery system that entraps natural bioactive substances, the bioavailability of phytochemicals, the challenges and limitations of standard cancer therapy, and recent patents on nanoparticle formulations containing a natural anti-cancer molecule.